Peran Aktif Bimbingan dan Konseling dalam Peningkatan Kualitas Pendidikan Madrasah Aliyah - Eko Wahyu Haderani; Nur Sofianto (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2021)
The role of guidance and counseling in coaching individual students in solving problems, challenges, and difficulties is a demand that must be given by the guidance and counseling program in the madrasah. The implementation of counseling guidance at Madrasah Aliyah Negeri throughout Banjarmasin has not yet been implemented in accordance with the objectives and functions of counseling guidance. The application of guidance and counseling is still visible in the routine curriculum of guidance and counseling activities. So that many types of main activities in counseling have not been implemented optimally. This research method is descriptive qualitative research on the role of guidance and counseling in public madrasah aliyah throughout Banjarmasin. This study provides a description of how the pattern of guidance and counseling in state madrasah aliyah throughout the city of Banjarmasin. The result of this research is that counseling guidance at state madrasah Aliyah throughout Banjarmasin has played an active and optimal role in carrying out preventive, curative, or corrective functions and perseverative functions, which have positive implications for achieving optimal educational goals and improving the quality and quality of education in State Madrasah Aliyah throughout the city of Banjarmasin.